Pertumbuhan dan daya hasil beberapa genotipe jagung merah Unipa di Distrik Sentani Kabupaten Jayapura - Wara, Veronica; Mawikere, Nouke Lenda; Purnomo, D. Wasgito; Prabawardani, Saraswati; Ilona Noya, Alce; Heskiel Wospakrik, Andrean (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: This study aims to determine the growth and yield of several genotypes of Unipa red corn. The research was conducted in the Sentani District, Jayapura Regency, from October 2021 to February 2022. The experiment was laid out in a Randomized Block Design (RBD) with a single treatment factor, consisting of 9 Unipa red corn genotypes, 1 local Jayapura genotype, and 1 national genotype. The observed variables included plant height, stem diameter, number of stem segments, length of stem segments, harvest age, cob length without husks, cob weight without husks, cob diameter without husks, weight of 100 seeds, seed weight per plot, seed weight per hectare, and seeds/cobs color. The results showed that: 1) The growth components of 11 corn genotypes vary greatly, and genotype treatment significantly affects the characteristics of plant height 7 MST, stem diameter 7 MST, and stem internode length; 2) The Unipa AMP-6 genotype had the highest productivity of 6.57 tons/ha; 3) The average harvest age of Unipa AMP corn was 87-88 days after planting; and 4) The genotype with the largest percentage of homogeneous seed color was AMP Unipa-8 (90.44%).